Targeting the epigenome: Screening bioactive compounds that regulate histone deacetylase activity - Godoy, Luis D. (Mol Nutr Food Res, 2017)
SCOPE: Nutrigenomics is a rapidly expanding field that elucidates the link between diet-genome interactions. Recent evidence demonstrates that regulation of the epigenome, and in particular inhibition of HDACs, impact pathogenetic mechanisms involved in chronic disease. Few studies, to date, have screened libraries of bioactive compounds that act as epigenetic modifiers. This study screened a library of 131 natural compounds to determine bioactive compounds that inhibit Zn-dependent HDAC activity. METHODS AND RESULTS: Using class-specific HDAC substrates, we screened 131 natural compounds for HDAC activity in bovine cardiac tissue. From this screen, we identified 18 bioactive compound HDAC inhibitors. Using our class-specific HDAC substrates, we next screened these 18 bioactive compounds against recombinant HDAC proteins. Consistent with inhibition of HDAC activity, these compounds were capable of inhibiting activity of individual HDAC isoforms. Lastly, we report that treatment of H9c2 cardiac myoblasts with bioactive HDAC inhibitors was sufficient to increase lysine acetylation as assessed via immunoblot. CONCLUSION: This study provided the first step in identifying multiple bioactive compound HDAC inhibitors. Taken together, this report sets the stage for future exploration of these bioactive compounds as epigenetic regulators to potentially ameliorate chronic disease.